Evolution of gastric surgery techniques and outcomes. Issue 1 (December 2016) - Shiozaki, Hironori; Shimodaira, Yusuke; Elimova, Elena; Wadhwa, Roopma; Sudo, Kazuki; Harada, Kazuto; Estrella, Jeannelyn; Das, Prajnan; Badgwell, Brian; Ajani, Jaffer
Abstract Surgical management of gastric cancer improves survival. However, for some time, surgeons have had diverse opinions about the extent of gastrectomy. Researchers have conducted many clinical studies, making slow but steady progress in determining the optimal surgical approach. The extent of lymph node dissection has been one of the major issues in surgery for gastric cancer. Many trials demonstrated that D2 dissection resulted in greater morbidity and mortality than D1 dissection. However, long-term outcomes demonstrated that D2 dissection resulted in longer survival than D1 dissection. In 2004, the Japan Clinical Oncology Group reported a pivotal trial which was performed to determine whether para-aortic lymph node dissection combined with D2 dissection was superior to D2 dissection alone and found no benefit of the additional surgery. Gastrectomy with pancreatectomy, splenectomy, and bursectomy was initially recommended as part of the D2 dissection. Now, pancreas-preserving total gastrectomy with D2 dissection is standard, and ongoing trials are addressing the role of splenectomy. Furthermore, the feasibility and safety of laparoscopic gastrectomy are well established. Survival and quality of life are increasingly recognized as the most important endpoints. In this review, we present perspectives on surgical techniques and important trials of these techniques in gastric cancer patients.